(untitled) (Research, Society and Development, 2022)
Brazil is a country full of diversity and home to different indigenous tribes with cultural and ethnic traditions distinct from the rest of society, for the indigenous woman, pregnancy is seen as a dream, which transcends the supernatural world. In this context, the present work aims to describe the practices and culture of indigenous women through their gestational, prenatal, childbirth and puerperium processes. This is a quanti-qualitative narrative literature review study, which used data available in the Live Births Information System - SINASC and articles published in Google Scholar and SciELO databases. It is observed that the indigenous population is in vulnerability, where it has a high fertility rate and maternal mortality ratio, in relation to prenatal care most indigenous women had 7 more consultations, it is important to note that in the country, health conditions and cultural and socioeconomic influences influence the choice of type of delivery, and among indigenous women in the period from 2018 to 2020, vaginal delivery was the most recurrent, and most deliveries took place. in a hospital environment. Thus, it is necessary to have a different view of health professionals in relation to indigenous women, so that their ethnic and cultural aspects are respected even in the hospital environment.